2021
DOI: 10.1007/jhep01(2021)024
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoscalar glueballs in the Klebanov-Strassler theory

Abstract: In this paper we describe a pseudoscalar subsector of the Klebanov-Strassler model. This subsector completes the holographic reconstruction of the spectrum of the lowest-lying glueball states, which are singlet under the global symmetry group SU(2) × SU(2). We derive the linearized supergravity equations for the pseudoscalar fluctuations and analyze their spectrum. The system of equations is shown to be compatible with six eigenmodes, as expected from supersymmetry. Our numerical analysis allows to reliably ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 56 publications
(154 reference statements)
0
12
0
Order By: Relevance
“…Notwithstanding supersymmetry, the mentioned properties of the Klebanov-Strassler theory make it the most suitable candidate for the holographic study of the glueball sector of JHEP11(2022)164 shown, as well as the references to the works, from which the values are extracted. For the scalar sector, the assignment was made based on the analysis of [72,80]. These masses are compared with the masses recently obtained for the SU(∞) bosonic Yang-Mills on the lattice [28] (right table).…”
Section: Jhep11(2022)164mentioning
confidence: 99%
See 4 more Smart Citations
“…Notwithstanding supersymmetry, the mentioned properties of the Klebanov-Strassler theory make it the most suitable candidate for the holographic study of the glueball sector of JHEP11(2022)164 shown, as well as the references to the works, from which the values are extracted. For the scalar sector, the assignment was made based on the analysis of [72,80]. These masses are compared with the masses recently obtained for the SU(∞) bosonic Yang-Mills on the lattice [28] (right table).…”
Section: Jhep11(2022)164mentioning
confidence: 99%
“…The spectrum of singlet fluctuations of the Klebanov-Strassler background was studied in a series of papers including [63][64][65][66][67][68][69][70][71][72]. (See also [73][74][75][76][77][78][79] for the studies of non-singlet states or deformations of the Klebanov-Strassler theory.)…”
Section: Jhep11(2022)164mentioning
confidence: 99%
See 3 more Smart Citations